2020
DOI: 10.7717/peerj.8653
|View full text |Cite
|
Sign up to set email alerts
|

Screening and identification of critical biomarkers in erectile dysfunction: evidence from bioinformatic analysis

Abstract: Purpose Erectile dysfunction (ED) is one of the most common male-disease globally. Despite efforts to explain its pathogenesis, the molecular mechanisms of ED are still not well understood. Methods The microarray dataset GSE10804 was downloaded from the Gene Expression Omnibus (GEO) to find candidate genes in ED progression. After differentially expressed genes (DEGs) were identified, functional enrichment analysis was performed. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 37 publications
(41 reference statements)
2
4
1
Order By: Relevance
“…Still, there have been a few studies of human tissues. [ 65 ] GO and KEGG pathway enrichment analysis of hub DEGs in human's ED samples showed that extracellular exosome in CC and collagen fibril organization in BP had the same downward trend compared with our present data. [ 65 ]…”
Section: Discussionsupporting
confidence: 77%
“…Still, there have been a few studies of human tissues. [ 65 ] GO and KEGG pathway enrichment analysis of hub DEGs in human's ED samples showed that extracellular exosome in CC and collagen fibril organization in BP had the same downward trend compared with our present data. [ 65 ]…”
Section: Discussionsupporting
confidence: 77%
“…CLDN11 encodes a member of the claudin family, and claudins are integral membrane proteins and components of tight junction strands (Gumbiner, 1996). In our study, Cldn17 mRNA expression in the DMED group was higher than that in the NC group, and KEGG enrichment analysis showed (Hui et al, 2020). However, they did not found the role of CLDN11 in junctional and barrier integrity.…”
Section: Discussioncontrasting
confidence: 63%
“…In our study, Cldn17 mRNA expression in the DMED group was higher than that in the NC group, and KEGG enrichment analysis showed upregulation of genes related to ECM–receptor interaction. Hui et al reanalysed the chip data published by Wessells et al's study and identified 618 DEGs and the enriched pathways of DEGs included ECM–receptor interaction(Hui et al., 2020). However, they did not found the role of CLDN11 in junctional and barrier integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, microarray technology and bioinformatics analysis have become popular methods of exploration of disease pathogenesis and identification of biomarkers for disease progression [ 22 ]. The purpose of this study is to identify potential molecular targets and signaling pathways associated with IDD based on Gene Expression Omnibus datasets.…”
Section: Introductionmentioning
confidence: 99%